Enrollment Issue, Power Energy Management Approach and Structure of Control of Renewable Energy Microgrid: A Review - Mohd Fauzi, Mohamad Yusof; Abu Zaharin, Ahmad (Penerbit Universiti Malaysia Pahang, 2019)
The integration and emerging of distributed generation into the grid especially renewable energy RE source has brought solution of the problem increasing demand of electricity. The utilization of renewable energy as a source generation can minimize the effect of green house and reduce the cost of operation. The RE microgrids are the great power solution due to the capability to control and coordinate different level between the loads and generators. The energy management control is the key of successions to provide the power reliability in the RE microgrid. The problem of the optimal energy management has become widely investigated in order to achieve the optimize architecture structure of RE microgrid. Thus in this paper the details description of RE microgrid, problem issue and brief explanation about power energy management control are discussed. Furthermore, the architecture control technique of RE microgrid are elaborated and list of control technique from previous research are details. The progression project of microgrid in the world was reported and suggestion of area interest for future research activity are presented briefly